2013
DOI: 10.1902/jop.2013.120451
|View full text |Cite
|
Sign up to set email alerts
|

Coronally Advanced Flap Alone or With Connective Tissue Graft in the Treatment of Single Gingival Recession Defects: A Long‐Term Randomized Clinical Trial

Abstract: Both surgical procedures were effective in the treatment of single Miller Class I and II GR defects. The CAF+CTG procedure provided better long-term outcomes (60 months postoperatively) than CAF alone. Long-term stability of the gingival margin is less predictable for Miller Class II GR defects compared to those of Class I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 22 publications
(82 reference statements)
6
34
0
3
Order By: Relevance
“…A total of 101 articles 30‐131 with 94 RCTs potentially eligible for inclusion into the pooled estimates were identified in the base of evidence, and their main characteristics (i.e., number and age of participants, interventions, follow‐up period, number of sites exhibiting CRC, MRC [percentage], use of RMAs, randomization, allocation concealment, masking of examiners, completeness of the follow‐up period, and risk of bias) are depicted in Table 2 30‐131 . Seven studies were reported in two articles each, and their data were reported under one study name 37,38,57,58,65,66,83,84,90,91,110,111,115,116 …”
Section: Summary Of What Other Srs Have Evaluatedmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 101 articles 30‐131 with 94 RCTs potentially eligible for inclusion into the pooled estimates were identified in the base of evidence, and their main characteristics (i.e., number and age of participants, interventions, follow‐up period, number of sites exhibiting CRC, MRC [percentage], use of RMAs, randomization, allocation concealment, masking of examiners, completeness of the follow‐up period, and risk of bias) are depicted in Table 2 30‐131 . Seven studies were reported in two articles each, and their data were reported under one study name 37,38,57,58,65,66,83,84,90,91,110,111,115,116 …”
Section: Summary Of What Other Srs Have Evaluatedmentioning
confidence: 99%
“…Of the 94 trials included in Table 2, 52 were included in the following sets of meta‐analyses: 1) ADMG/CM + CAF versus SCTG‐based procedures; 31,66,76,97,102,114 2) ADMG/CM + CAF versus CAF; 57,58,86,125 3) BS + GTR with resorbable membranes (RS) + CAF versus GTR with RS + CAF; 62,63,78,101 4) EMD + CAF versus CAF; 51,53,59,71,94,103,115,116 5) EMD + CAF versus SCTG + CAF; 30,32,90,91 6) GTR with RS + CAF versus CAF; 36,83,84 7) GTR (all types of membrane) + CAF versus SCTG‐based procedures; 35,43,55,74,96,101,107,109,117,122,123,126 8) SCTG‐based procedures versus CAF; 40,41,54,56,80 9) SCTG + CAF versus SCTG (epithelial collar); 44,47 10) SCTG‐based procedures, micro versus macro procedures; 42,46 and 11) SCTG‐based procedures versus FGG 70,100 . All of the comparisons were performed using studies reporting data on single defects, except for one comparison on EMD + CAF versus CAF 53,71 that could also be conducted using data on multiple recessions.…”
Section: Summary Of What Other Srs Have Evaluatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional research on outcomes in Miller Class III and IV defects is needed. Data reporting should be stratified by Miller Class 5 . 3) There is limited evidence on patient‐reported outcomes.…”
Section: Research Priorities For the Futurementioning
confidence: 99%
“…Foi verificado que a cirurgia plástica periodontal, por meio de enxertos autógenos de tecido, tem sido mais efetiva no tratamento das recessões gengivais [3][4][5] . Existem diversas técnicas cirúrgicas para recobrimento radicular: retalho deslocado coronal (RDC), Deslizamento Lateral do Retalho (DLR), Enxerto Gengival Livre (EGL) e Enxerto de Conjuntivo Subepitelial (ECSE) 5,6 . O tratamento depende de um exame periodontal em que serão observados os seguintes parâmetros clínicos na região onde ocorre a recessão gengival: a quantidade de gengiva inserida e sua espessura, a presença ou a ausência de profundidade clínica de sondagem (PCS), o nível clínico de inserção (NCI), o contato oclusal prematuro e a classificação da recessão de acordo com Miller 7 .…”
Section: Introductionunclassified